Probiotic Pseudomonas communities enhance plant growth and nutrient assimilation via diversity-mediated ecosystem functioning. (October 2017) - Hu, Jie; Wei, Zhong; Weidner, Simone; Friman, Ville-Petri; Xu, Yang-Chun; Shen, Qi-Rong; Jousset, Alexandre
Abstract: Plant-associated microbes play an important role in plant growth and development. While the introduction of beneficial microbes into the soil could improve plant production in low-input agricultural systems, real-world applications are still held back by poor survival and activity of the probiotic microbes. In this study, we used a biodiversity-ecosystem functioning (BEF) framework to specifically test how Pseudomonas community richness shapes the bacterial inoculant survival and functioning in terms of plant growth. To this end, we manipulated the richness of a probiotic Pseudomonas spp. bacterial community inoculant (1, 2, 4 or 8 strains per community) and compared diversity and strain identity effects on plant biomass production and nutrient assimilation in vivo with tomato. We found that increasing the richness of the bacterial inoculant enhanced the survival and abundance of Pseudomonas communities leading to higher accumulation of plant biomass and more efficient assimilation of nutrients into the plant tissue. Diversity effects were clearly stronger than the Pseudomonas strain identity effects and diversity-mediated plant growth promotion could be linked with increased production of plant hormones, siderophores and solubilization of phosphorus in vitro . Together these results suggest that multi-strain microbial inoculants can promote plant growth more reliably and effectively compared to single-strain inoculants. Highlights: Multi-strain inoculants improve plant growth better than single-strain inoculants. Richness effects were clearly stronger than the Pseudomonas strains identity effects. Multi-strain inoculants enhance inoculants' abundance in the rhizosphere. Plant growth linked with plant hormones, siderophores and phosphorus solubilization.